2013
DOI: 10.1542/peds.2013-2049
|View full text |Cite
|
Sign up to set email alerts
|

National, Regional, and State Abusive Head Trauma: Application of the CDC Algorithm

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Abusive head trauma (AHT) is a rare phenomenon that results in devastating injuries to children. It is necessary to analyze large samples to examine changes in rates over time. WHAT THIS STUDY ADDS:This is the first study to examine rates of AHT at the national, regional, and state level. The results provide a more detailed description of AHT trends than has been previously available. abstract OBJECTIVE: To examine national, regional, and state abusive head trauma (AHT) trends usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 17 publications
2
56
0
1
Order By: Relevance
“…1,15 As noted in Shanahan et al, it is also possible that differences in ICD-9-CM coding practices affect the rates reported by authors using administrative databases. 25 In a preliminary exploration of the KID database, we found that northern states were much more likely to document SBS than western states (54.8% vs 35.0%, p = 0.004). Other possible explanations for the differences in reported cases may be other external factors such as economy or unemployment, which can vary across regions.…”
Section: Discussionmentioning
confidence: 82%
“…1,15 As noted in Shanahan et al, it is also possible that differences in ICD-9-CM coding practices affect the rates reported by authors using administrative databases. 25 In a preliminary exploration of the KID database, we found that northern states were much more likely to document SBS than western states (54.8% vs 35.0%, p = 0.004). Other possible explanations for the differences in reported cases may be other external factors such as economy or unemployment, which can vary across regions.…”
Section: Discussionmentioning
confidence: 82%
“…4 A retrospective study using the Centers for Disease Control and Prevention definition of AHT demonstrated a rate of ∼1 in 3000 infants. 5 Studies in other countries suggest similar incidences. 6,7 Proper diagnosis of mild AHT is difficult because caretakers rarely provide an accurate history, 8 infants present with nonspecific symptoms, such as vomiting or fussiness, and physical examination is often normal.…”
mentioning
confidence: 85%
“…4 La incidencia del traumatismo encefalocraneano abusivo es imprecisa y subestimada; según autores, oscila entre 11 y 40,5 casos por cada 100 000 niños por debajo del año de edad. [5][6][7] Las lesiones encefálicas derivadas de este síndrome son las que habitualmente conducen a estos pacientes a una situación de muerte cerebral.…”
Section: Donación De óRganos Tras Muerte Encefálica Debida a Maltratounclassified